The Immunosuppressant Tacrolimus (FK506) Facing the 21st Century: Past Findings, Present Applications and Future Trends - Carlos Barreiro; Ana Ibañez; Sonia Garrido-Chamorro; José Luis Barredo (Fermentation)
The confluence of a large variety of factors, achievements and developments has resulted in the current long-term success in graft transplants. Some of these events are reviewed, paying special attention to immunosuppressant drugs, which are one of the most relevant milestones in the prevention of organ transplant rejection. The discovery, industrial exploitation, mechanisms of action and side effects of several drugs exhibiting immunosuppressive effects (e.g., corticosteroids, nitrogen mustards, mycophenolic acid, rapamycin) are deeply detailed. Furthermore, new trends in immunosuppressant research, improvement and reformulation are also reviewed. Nevertheless, the core of the manuscript is the immunosuppressant tacrolimus, also called FK506, which has been sought after due to the commercial success of cyclosporine and other immunosuppressant compounds, but also because of the side effects of those previous compounds. Thus, in the mid-1980s tacrolimus was described as a more potent immunosuppressive molecule, with less undesirable effects. Currently, tacrolimus is a well-stablished API that is used as a clinical treatment to avoid graft rejection, but also shows interesting properties in terms of decreasing the impact of some autoimmune diseases and acting as an enhancer of nerve regeneration treatments. Thus, in the 40th anniversary of its discovery, this paper describes the current state of the art of this drug and how it is adapting to new social needs and clinical trends.